COMBINING ABILITY ANALYSIS FOR YIELD AND PHYSIOLOGICAL DROUGHT RELATED TRAITS IN TOMATO (SOLANUM LYCOPERSICUM L.) UNDER MOISTURES STRESS - PEDAPATI, ANITA; R. V. S. K. REDDY; J. DILIP BABU; KUMAR, S. SUDHEER; N. SUNIL (The Bioscan, 2013)
Eighteen parents were crossed in line X tester fashion comprising 15 lines and 3 testers to estimate combining ability in tomato for fruit yield, yield components and drought tolerant traits. F1 and parents were evaluated under stress (10 days and 15 days irrigation interval) and irrigated conditions. For fruit yield per plant, the top five crosses EC310301 X EC164654 (251.33), EC 251578 X EC 164654 (304.82), IC249512 X IC249503 (381.70), EC162516 X IC249503 (468.85) and EC164845 X IC249505 (571.92) having high and positively significant sca effects under irrigated normal condition. Whereas, in stressed condition IC249512 X IC249503 (258.06), IC249512 X EC164654 (260.16), EC310301 X EC164654 (314.06), EC162516 X IC249505 (388.34) and EC164845 X IC249505 (469.54) having high and positively significant sca effects. Based on results, the genotypes EC251578, IC249512, EC162516, EC249503 and EC164654 recorded high positive gca effects. IC249512, EC164845, EC249505 and EC164654 are ideal choice for yield under stressed condition. IC249512 was good performer for most of the traits in both irrigated and stressed conditions. Three parents EC162516, EC249505 and EC168096 are identified as good general combiners with high yield potential in drought environment. So, these lines are reliable for further drought tolerance breeding.